Exploring Customer Loyalty from an Image and Satisfaction Perspective: A Case Study of Traditional Culinary in Yogyakarta - Catur Widayati; Tri Jayanti; Hendra Wiyanto; Herlina Budiono; Ikhyandini Garindia Atristyanti (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to examine and analyze the effect of Cognitive Image, Unique Image, and Affective Image on Customer Loyalty through Satisfaction as a mediating variable among visitors of Mie Jowo Mbah Gito in Yogyakarta. The population in this study consists of the community or customers of Mie Jowo Mbah Gito who have made at least two purchases in the last six months, with a sample size of 110 based on the Heir formula. This research is a quantitative study with data collection using a survey method. Data analysis is performed using Partial Least Squares (PLS) 4. he results of the study show that: 1) Affective Image has a significant positive effect on customer satisfaction, meaning that improving affective Image can increase customer satisfaction. 2) Affective Image also has a significant effect on customer loyalty, indicating that a good affective Image can enhance customer loyalty. 3) Customer satisfaction has a significant positive effect on customer loyalty, meaning that the higher the customer satisfaction, the higher the loyalty level. 4) Cognitive Image has a significant positive effect on customer satisfaction, meaning that a strong cognitive Image can improve customer satisfaction. 5) Cognitive Image also has a significant positive effect on customer loyalty, indicating that strong belief in cognitive Image will strengthen customer loyalty. 6) Unique Image has a significant positive effect on customer satisfaction, meaning that a good unique Image can increase customer satisfaction. 7) Unique Image also has a significant positive effect on customer loyalty, indicating that a strong unique Image can enhance customer loyalty. 8) Customer satisfaction mediates the effect of cognitive Image on customer loyalty. 9) Customer satisfaction also mediates the effect of unique Image on customer loyalty. 10) Customer satisfaction mediates the effect of affective Image on customer loyalty. This study provides an important contribution in understanding the relationship between the Image formed by Mie Jowo Mbah Gito and customer satisfaction and loyalty.